ESL undergraduates' experience of Wiki and Skype for collaborative learning - Hiew, Yolanda Lee Lee; Tan, Bee Hoon; Yap, Ngee Thai; Mohd Kasim, Zalina (Universiti Putra Malaysia Press, 2014)
In recent years, university instructors are required to integrate computer technologies in their teaching and to support student learning by employing computer-mediated communication (CMC) tools. Yet, the authentic experience of students’ engagement with the technology is seldom explored. There is an apparent lack in research related to student satisfaction and their perceived usefulness of the CMC application for task completion in the public tertiary sector. Thus, this paper examines students’ experience in using Wiki and Skype to complete two project-based tasks collaboratively. The sample comprised 25 ESL undergraduates from an intact class. Class observation, interview and a questionnaire with Likert-scale and open-ended items were administered for the investigation. Data from the questionnaire only are reported here due to space constraint. The results indicated that Skype is preferred over Wiki for interaction; however, the use of Wiki was more favorable as it can improve students’ writing skills. Skype was perceived as more useful than Wiki for academic, social and technological aspects. Students also commented on the technological problems where poor Internet connection was the main interruption that caused delay in their work.